2021
DOI: 10.1038/s41598-021-90649-x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the odorant coreceptor Orco impairs foraging and host finding behaviors in the New World screwworm fly

Abstract: The evolution of obligate ectoparasitism in blowflies (Diptera: Calliphoridae) has intrigued scientists for over a century, and surprisingly, the genetics underlying this lifestyle remain largely unknown. Blowflies use odors to locate food and oviposition sites; therefore, olfaction might have played a central role in niche specialization within the group. In insects, the coreceptor Orco is a required partner for all odorant receptors (ORs), a major gene family involved in olfactory-evoked behaviors. Hence, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Further functional work in MsigOrco would allow a better understanding of ion channel formation. The highly conserved sequence of Orco and its unique position in olfactory recognition indicates that it could potentially be used as a target gene for the future development of novel and effective control strategies [45][46][47]. RT-qPCR results showed that MsigOR22 and MsigOR30 were preferentially expressed in female antennae, which may be involved in the regulation of female oviposition.…”
Section: Plos Onementioning
confidence: 99%
“…Further functional work in MsigOrco would allow a better understanding of ion channel formation. The highly conserved sequence of Orco and its unique position in olfactory recognition indicates that it could potentially be used as a target gene for the future development of novel and effective control strategies [45][46][47]. RT-qPCR results showed that MsigOR22 and MsigOR30 were preferentially expressed in female antennae, which may be involved in the regulation of female oviposition.…”
Section: Plos Onementioning
confidence: 99%
“…Work on insect genomes continued, with exploration of odorant-binding proteins (OBPs) and odorant receptors, thus introducing semio-chemical options (Venthur and Zhou 2018). For example, (i) the oviposition preference of Drosophila melanogaster could be shifted by introducing OBP57d/e genes from D. sechellia (Matsuo et al 2007), (ii) in Rhodnius prolixus, the vector of Chagas disease, oviposition and blood ingestion were reduced by knockdown of ORco, a major gene family involved in olfactory-evoked behaviours of insects and a required partner for all odorant receptors (Franco et al 2016), and (iii) in Cochliomyia hominivorax, the response to floral-like and animal host-associated odours was impaired in ORco mutants that lost their odorant receptor function (Paulo et al 2021).…”
Section: Exploring Genomic Solutionsmentioning
confidence: 99%
“…While invertebrates can access multiple sensory modalities, the odor remains one of the most important cues for foraging. 11 , 12 , 13 , 36 Unsurprisingly, in Drosophila larvae and C. elegans , sensing food odors confers a fitness advantage by allowing animals to detect scattered food sources or through odor‐dependent alterations in the organismal metabolism that result in prolonged lifespans. 37 Furthermore, odor‐sensory cues are vital for the efficient localization of food sources in specific niches.…”
Section: Exploration—odor As a Cuementioning
confidence: 99%